Potentials and limitations to the biological nitrogen contribution from forage legumes in sub-Saharan Africa - Haque, I.; Jutzi, S.C. (Nairobi Rhizobium Microbiological Resources Centre, 1984)
Reviews the present state of knowledge about the biological fixation of N by forage legumes in sub-Saharan Africa; indicates the main factors limiting the contribution of biological Nitrogen to soils by forage legumes; highlights the potentials of legume - food crop - livestock interactions in various production systems; and lastly suggests the areas where intesified research is justified in terms of scientific and practical benefits.